The learning gap : - Stevenson, Harold W. (Summit Books, 1992)
Quantifiable variables include instruction time, test data, length of school year, curriculum studied, and instruction strategies. Another factor the authors consider is attitude (e.g., parental attitudes toward schooling, children toward learning, society toward educators, etc.). The writing style is informal, and sufficient statistical data is presented to support the findings. Some challenges are offered: "The American educational system as it currently exists is producing an educationally advantaged minority and a disadvantaged majority."